Neutron powder diffraction study at high temperature of the Ruddlesden-Popper phase Sr3Fe2O6 + δ - Prado, Fernando Daniel (2007)
The crystal and oxygen defect structure of the n = 2 Ruddlesden-Popper phase Sr3Fe2O6 + δ have been studied by in situ high temperature neutron powder diffraction in the temperature range 20 ≤ T ≤ 900 °C in air. The analysis of the neutron diffraction data revealed the presence of structural oxygen vacancies on both the O(1) sites linking the octahedra along the c axis and the O(3) sites in the FeO2 planes of the perovskite layers. The oxygen vacancies on the O(3) site increase with temperature up to ∼ 0.25 per formula unit at T = 900 °C. This result supports previously proposed oxygen ion diffusion mechanism in Sr3Fe2O6 + δ that involves the migration of vacancies from an O(3) site to an adjacent O(1) site. The total linear expansion along the c axis αc = 17.7(5) · 10- 6 K- 1 mainly affects the perovskite block while the width of the rock salt layers remains stable with temperature. The total volumetric expansion αV / 3 = 20(1) · 10- 6 K- 1 is around the average of the TEC values (14.8-27.1 K- 1) reported for the perovskite system La1 - xSrxCo1 - yFeyO3 - δ.